« Djutha », nécropole de la période de la Horde d’Or dans le village caucasien de Djuhti, région de Stavropol - Zvezdana Dodé (Archéologie Médiévale)
The 13th and 14th centuries in the North Caucasus are marked by the domination of the Mongol Empire of the Golden Horde. The region is an interesting observatory of the active ethnic mixing between the nomadic and urban populations, while we note the essential role of the nomads. The Tartars from Mongolia brought to the Caucasus cultural elements such as brocades, belt fittings, hair ornaments and weapons from Central Asia, China and the Western Iranian world. All of these bear witness to the traditions of the populations subjugated by the Mongols. Other sites dating to the period of the Golden Horde, for example Madjari, Beloretchenski, Djulat etc., have yielded archaeological artefacts similar to those found in graves in the region of the Volga or in the Djuhta kurgans. The grave goods from this necropolis give an insight into the principal characteristics of the Imperial culture of the Horde d’Or.